REGULARITIES OF DEVELOPMENT AND STUDY OF FLORISTIC COMPOSITION OF ALGAE - M.I. Mustafayeva; G.U.Sagdullayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The hydrochemical composition of pond water, which plays a major role in the development and formation of algae flora, has been clarified; as a result, it has been established that the pollution of ponds with organic, mineral and toxigenic substances increases from municipal and industrial wastewater. This changes the species composition of the water. An ecological and sanitary assessment of biological ponds is given based on the species composition of algae. Comparative analyzes of the algal flora of biological ponds of treatment facilities in the city of Bukhara with a similar flora of ponds in Uzbekistan and a detailed study of the algae flora of biological ponds of treatment facilities of the city of Bukhara are given.